A Study on the Current Situation of the Development of Kindergarten Physical Intelligence Curriculum in Enshi Prefecture - Shen, Li (Pacific International Journal, 2023)
Abstract: This study presents survey data and interview results from experts at Wuhan Happy Smart Beans Culture Communication Co., Ltd, a well-established children's body intelligence education and training institution in Enshi. The study investigates the current state of kindergarten body intelligence curriculum development, analyzing its policies, goal setting, activity content, organization, and evaluation of effectiveness. The findings contribute to a realistic understanding of early childhood physical intelligence curriculum research and teacher training for early childhood physical education teachers.